2004
DOI: 10.1007/s00109-004-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of metabotropic glutamate receptor�1, a G protein coupled receptor, in melanoma development

Abstract: Melanoma is the aberrant proliferation of melanocytes, the cells in the skin responsible for pigment production. In the United States the current lifetime risk of melanoma development is 1 in 57 in males and 1 in 81 in females. In its early stages melanoma can be surgically removed with great success; however, advanced stages of melanoma have a high mortality rate due to the lack of responsiveness to currently available therapies. The development of animal models to be used in the studies of melanoma will prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 126 publications
0
52
0
2
Order By: Relevance
“…All those findings indicate that alterations activating RAS/mitogen-activated protein kinase pathway are important events on melanoma development, 27 but also, that tumorigenesis mechanisms are different in different individuals depending on the their sun exposure pattern. mGluR1 is a GCPR, and, therefore, stimulation of this receptor might lead to the activation of MAPK pathway (revised by Marin and Chen 28 ). Until now, there is no evidence of which cascades could be triggered through the activation of this receptor in human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All those findings indicate that alterations activating RAS/mitogen-activated protein kinase pathway are important events on melanoma development, 27 but also, that tumorigenesis mechanisms are different in different individuals depending on the their sun exposure pattern. mGluR1 is a GCPR, and, therefore, stimulation of this receptor might lead to the activation of MAPK pathway (revised by Marin and Chen 28 ). Until now, there is no evidence of which cascades could be triggered through the activation of this receptor in human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This property places the EGFR as a downstream element in the signaling pathways of a variety of cell-surface receptors (Carpenter, 1999;Guerrero et al, 2004), most notably GPCRs coupled to Gi or Gq (Carpenter, 1999;Daub et al, 1997;Daub et al, 1996;Gschwind et al, 2001;Hackel et al, 1999;Wetzker and Bohmer, 2003). Abundant evidence suggests that GPCRs could be important regulators of cell growth and under certain circumstances can even act as oncoproteins (Marin and Chen, 2004;Marinissen and Gutkind, 2001;Parnot et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ectopic expression of a particular GPCR in a cell context that normally lacks the receptor can disrupt cell proliferation control and produce cell transformation in the presence of the corresponding ligand (Marin and Chen, 2004).…”
Section: B P2y 1 R Stimulates Egfr-mediated Mitogenesis Cell Prolifementioning
confidence: 99%
“…In addition, duplex RT-PCR analysis indicated that the mGluR1 (16). The same group characterized a mouse melanoma model, which has implicated the ectopic expression of mGluR1 in melanogenesis and metastasis (16,17). In continuation of these experiments Marín et al (18) showed in mouse melanoma cell lines that stimulation of mGluR1 results in inositol triphosphate (IP 3 ) accumulation and extracellular-regulated kinases 1 and 2 (ERK 1/2) activation, which both could be inhibited by pretreatment of the tumor cells with a mGluR1 subtype-specific competitive antagonist LY367385.…”
Section: Introductionmentioning
confidence: 99%